If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15X + 21 = 42 + 8X Reorder the terms: 21 + 15X = 42 + 8X Solving 21 + 15X = 42 + 8X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-8X' to each side of the equation. 21 + 15X + -8X = 42 + 8X + -8X Combine like terms: 15X + -8X = 7X 21 + 7X = 42 + 8X + -8X Combine like terms: 8X + -8X = 0 21 + 7X = 42 + 0 21 + 7X = 42 Add '-21' to each side of the equation. 21 + -21 + 7X = 42 + -21 Combine like terms: 21 + -21 = 0 0 + 7X = 42 + -21 7X = 42 + -21 Combine like terms: 42 + -21 = 21 7X = 21 Divide each side by '7'. X = 3 Simplifying X = 3
| 2[x+6]=10 | | 5x^2-7x=2 | | 0.5(2x+2)-0.25(3x-1)=15 | | 15x+25=42 | | 3x^2-5x=-6 | | 20v^2-11v=3 | | 15x^2+109x+8=0 | | 8x^2+51x+18=0 | | 3x-2(3x-2)=2(4-4)+3 | | 2x-x+7=10 | | 6x+2+x=1+4x+4 | | 4b+8=-16 | | 3x+2+5=30 | | 4x+9=50 | | 8x^2+23x-3=0 | | 3x*x+5x-7=0 | | x/3+2=7(x-2) | | x+x-6=8 | | 3(x-2)-(3-x)=5x+4 | | 2(x-2)=2-x | | x/6=-2 | | 2-(-8)= | | 3(x+6)-2=15 | | 9+9c=9 | | 5x-4=3x+3x+8 | | p+10+(p-19)+2*p=699 | | p+10+p+19-2p=699 | | 3x+8-2x=-24 | | 11x-6=3x+26 | | 4x^2-11x+5=-2x+3 | | 6x^2-7x-49=0 | | y=3x^2+12x+5 |